Đang tải thanh công cụ tìm kiếm ...
Phép Tính Online

Bài 7. Biến đổi thành tích các biểu thức sau

Bài 7. Biến đổi thành tích các biểu thức sau

a) 1 - sinx;                    b) 1 + sinx;

c) 1 + 2cosx;                  d) 1 - 2sinx  

Hướng dẫn giải:

 a) 1 - sinx = sin\( \frac{\prod }{2}\) - sinx = 2cos\( \frac{\frac{\prod }{2}+x}{2}\)sin\( \frac{\frac{\prod }{2}-x}{2}\)

                 = 2cos\( \left ( \frac{\prod }{4} +\frac{x}{2}\right )\)sin\( \left ( \frac{\prod }{4} -\frac{x}{2}\right )\)

a) 1 + sinx = sin\( \frac{\prod }{2}\) + sinx = 2sin\( \left ( \frac{\prod }{4} +\frac{x}{2}\right )\)cos\( \left ( \frac{\prod }{4} -\frac{x}{2}\right )\)

c) 1 + 2cosx = 2(\( \frac{1}{2}\) + cosx) = 2(cos\( \frac{\prod }{3}\) + cosx) = 4cos\( \left ( \frac{\prod }{6} +\frac{x}{2}\right )\)cos\( \left ( \frac{\prod }{6} -\frac{x}{2}\right )\)

d) 1 - 2sinx = 2(\( \frac{1}{2}\) - sinx) = 2(sin\( \frac{\prod }{6}\) - sinx) = 4cos\( \left ( \frac{\prod }{12} +\frac{x}{2}\right )\)sin\( \left ( \frac{\prod }{12} -\frac{x}{2}\right )\)